Analysis of Cyanide in Cassava with Different Storage Durations Using Visible Light Spectrophotometry and Ninhydrin Reagen - Emma Emawati; Silvan Maulana; Winasih Rachmawati (PT CENDEKIA SCIENCE AND TECHNOLOGY, 2025)
Cassava (Manihot esculenta Crantz) is the third most important staple food in Indonesia, after rice and corn. Although it offers numerous health benefits, cassava also contains potentially harmful compounds, such as cyanide. This study aimed to analyze cyanide levels in freshly harvested cassava and cassava stored for five days, using both qualitative and quantitative methods. The research gap identified is the limited data on how storaåge duration affects cyanide levels in cassava and its implications for food safety. To address this, the study used qualitative analysis with picrate paper and quantitative analysis through UV-Vis spectrophotometry, employing ninhydrin as the reagent. The qualitative results revealed that both freshly harvested cassava and cassava stored for five days tested positive for cyanide, as indicated by the formation of a red-brown color on the picrate paper. The quantitative analysis was preceded by method validation, which showed excellent performance, including linearity (r = 0.9982), detection limit (BD = 1.33 µg/mL), quantification limit (BK = 4.43 µg/mL), recovery rate (98.7%), and relative standard deviation (RSD = 1.53%). The cyanide content in freshly harvested cassava was found to be 4.94 µg/g, while the content in cassava stored for five days was 7.16 µg/g. Both cassava samples were found to be safe for consumption, as their cyanide levels were below the safety threshold of 10 ppm. This study provides valuable insights into the safe consumption of cassava, even with storage, underlining the importance of proper handling.